PENGARUH COGNITIVE-BASED TRUST DAN AFFECTIVE-BASED TRUST TERHADAP OCB DIMEDIASI POS DAN LMX - FITR, ANISA ARDILA; TJAHJADI, KAREL (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study is to analyse the effect of cognitive-based trust and affective-based trust on organizational citizenship behavior (OCB) through the mediation of perceived organizational support (POS) and leader-member exchange (LMX). This research uses purposive sampling technique. Data collection was carried out by distributing questionnaires to respondents and using a Likert scale. Survey participants consisted of 62 employees at Dinas Kesehatan Kota Bekasi. The analysis method used quantitative analysis method using SEM-PLS. The findings of the study suggest that cognitive-based trust has an influence on POS, POS has an influence on OCB and POS mediates cognitive-based trust on OCB. Affective-based trust has a direct influence on LMX, but LMX has no influence on OCB and LMX does not mediate affective-based trust on OCB.